2018
DOI: 10.30773/pi.2018.06.17
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and Central Metabolites Affecting Depression, Anxiety, Suicidal Ideation, and Anger in Complex Regional Pain Syndrome Patients Using a Magnetic Resonance Spectroscopy: A Pilot Study

Abstract: Objective This study investigated peripheral and central metabolites affecting depression, anxiety, suicidal ideation, and anger in complex regional pain syndrome (CRPS) patients. Methods Metabolite levels were determined in the right and left thalamus and insula, in 12 CRPS patients using magnetic resonance spectroscopy (MRS). Results There were positive correlations between valine (Val)/tNAA (N-acetylaspartate+N-acetylaspartylglutamate) and the anxiety, and a negative correlation between glutamine (Gln)/NAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, using functional imaging, in vivo clinical data provides direct evidence of altered glutamate concentrations in emotional dysregulation. Most studies reported elevated glutamate levels across different brain regions in subjects with anxiety disorders [ 22 , 23 , 24 , 25 , 26 ], while one study found positive correlations between glutamate levels and anxiety symptoms [ 27 ]. However, others reported lower glutamate concentrations in the anterior cingulate cortex (ACC) in participants with anxiety disorders [ 28 ], and a negative correlation between glutamate concentrations in ACC and the anxiety symptoms [ 29 ].…”
Section: Potential Impacts Of Decreased Brain Glutamate In Msudmentioning
confidence: 99%
“…Furthermore, using functional imaging, in vivo clinical data provides direct evidence of altered glutamate concentrations in emotional dysregulation. Most studies reported elevated glutamate levels across different brain regions in subjects with anxiety disorders [ 22 , 23 , 24 , 25 , 26 ], while one study found positive correlations between glutamate levels and anxiety symptoms [ 27 ]. However, others reported lower glutamate concentrations in the anterior cingulate cortex (ACC) in participants with anxiety disorders [ 28 ], and a negative correlation between glutamate concentrations in ACC and the anxiety symptoms [ 29 ].…”
Section: Potential Impacts Of Decreased Brain Glutamate In Msudmentioning
confidence: 99%
“…Alterations in the function and structure of the brain were observed in patients with DPN. N-acetyl aspartate was decreased in the thalamus of patients with DPNP (46), and reduced inhibition of central nervous system might be associated with psychological comorbidities (47)(48)(49). A decrease in serum brain-derived neurotrophic factor (BDNF), a neurotrophin family member, is associated with peripheral neuropathy in patients with type 2 diabetes (50).…”
Section: Discussionmentioning
confidence: 99%
“…Central and peripheral metabolites in patients with complex regional pain syndrome were analyzed for their association with psychological disorders, including anxiety [ 85 ]. Specific associations were observed, which might show pathological interactions between a painful body and increases in anxiety in this population.…”
Section: Metabolomics To Differentiate Healthy and Anxiety Subjectmentioning
confidence: 99%
“…As lower NAA levels have been observed in patients with complex regional pain syndrome before, neuronal cell death may affect anxiety symptoms in this population [ 86 , 87 ]. In addition, peripheral CO 2 was positively associated with anxiety, which might be explained by an increase in sensory pain levels due to increased partial CO 2 pressure causing a synergistic boost of neuropsychiatric symptoms, such as anxiety [ 85 ].…”
Section: Metabolomics To Differentiate Healthy and Anxiety Subjectmentioning
confidence: 99%